Changes of human resource practice between Warid Telecom and Airtel Bangladesh Limited after merger and acquisition - Aziz, Saleha Farhaz (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.